Pengaruh Penggunaan Media Audio Visual Terhadap Hasil Belajar Siswa Pada Pembelajaran Tematik Di Kelas V SDN 16 Kota Bengkulu - Muhammad Daifullah Harits; Sri Dadi; Lukman (Universitas Bengkulu, 2022)
This study aims to determine and analyze the effect of using audio-visual media on student learning outcomes in thematic learning at SDN 16 Bengkulu City. This type of research is quantitative research and the method used is a quasi-experimental method with a research design of The Matching Only Pre-Test-Post Test Group Design. The population of this study were all fifth grade students with a sample based on the Cluster Random Sampling technique. The instrument used is a written test and data collection techniques in the form of pre-test and post-test. The data obtained were analyzed using quantitative analysis. The results of the post-test analysis showed a significant difference between the experimental class and the control class. Then the hypothesis test (t-test) was conducted with the number of Indonesian language subjects tcount (3.730) > ttable (1.670) and in science subjects tcount (3.231) > ttable (1.670). Based on the tcount > ttable, H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an effect of using audio-visual media on learning outcomes in thematic learning at SDN 16 Bengkulu City.